Islamisasi Jawa Bagian Selatan: Studi Masjid Gala Sunan Bayat Klaten - Retno Kartini Savitaningrum Imansyah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
This research on Masjid Gala Sunan Bayat Klaten aims at describing the Mosque Gala Sunan Bayat built in the sixteenth century in the effort of understanding the Islamization process in Klaten and its surroundings. Through the research, it is hoped to preserve the historical mosque and its role in the development of Islam. This research used a historical-archeological observation method. The data covers the origins of the mosque establishment and the condition of society at that time, architectural type, and historical objects within it beside understanding the development of the mosque since the establishment up to now. Data were collected through many sources, starting from interview with the key informant, document study and observation. The research result highlights that Gala Mosque was established on Jabalkat Hill by Sunan Pandangaran who was popularly called as Sunan Bayat (1512 M). Sunan Bayat is the disciple of Sunan Kalijaga who charges to spread Islam in Klaten regency and surrounds. This oldest mosque in Klaten has a strategic role in spreading Islamic teachings especially in philosophical teachings of “Patembayatan/ concordance” amongst Muslim, which is still going on up to now. Keywords: Gala Mosque, Sunan Bayat, Klaten.